SINTUWU MAROSO DALAM PENDIDIKAN MODERASI BERAGAMA - Uswatun Hasanah (Pusat Studi Gender dan Anak, IAIN Palu, 2023)
Sintuwu Maroso is the local wisdom of Poso City, containing moderation values which are believed to be one of the solutions in minimizing the possibility of religious conflicts in Poso City again. The purpose of the study was to analyze the implementation of Situwu Maroso in moderation education in schools. This research uses a descriptive qualitative approach with a type of field study research at SD-IT Hidayatullah Poso. Data collection techniques with interviews with several informants, namely principals, teachers, students then observe directly the learning process activities. The results showed that the values of sintuwu maroso in religious moderation education have been implemented in the learning process in schools, but have not been written in reality. The implementation of Sintuwu Maroso in religious moderation education is reflected in the aspects of: policies in the delivery of Tuwu Mombetubunaka (mutual respect), Tuwu Mombepomawo (living in mutual love), Tuwu Mombetatuwu (supporting each other / helping each other) through ceremonial activities and morning apples; in the learning process in the classroom, one of which is local content lessons; as well as extracurricular activities. Habituation and example are needed in implementing Sintuwu Maroso in religious moderation education. The local wisdom of